2010
DOI: 10.1111/j.1464-410x.2010.09737.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of medical therapy on transurethral resection of the prostate: two decades of change

Abstract: Study Type – Therapy (case series) 
Level of Evidence 4 What’s known on the subject? and What does the study add? Over the last several decades, medical therapy has usurped transurethral resection of the prostate (TURP) as the standard first line therapy for benign prostatic hyperplasia (BPH). The effect of this dramatic shift on the patients now presenting for TURP is generally unknown. Failure of medical therapy has now become one of the most important indications for TURP while those undergoing the proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 10 publications
5
45
2
Order By: Relevance
“…Since the introduction of pharmacological treatment, the rate of TURP has been in decline. 1 TURP remains the dominant form of surgery for BPH in Canada. 2 The fundamental importance of this surgery explains why the Royal College of Physicians and Surgeons of Canada (RCPSC) 3 classifies TURP as a "List A" surgical procedure, wherein "the fully trained resident must be competent to individually perform" the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of pharmacological treatment, the rate of TURP has been in decline. 1 TURP remains the dominant form of surgery for BPH in Canada. 2 The fundamental importance of this surgery explains why the Royal College of Physicians and Surgeons of Canada (RCPSC) 3 classifies TURP as a "List A" surgical procedure, wherein "the fully trained resident must be competent to individually perform" the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Because most men present fi rst to their primary care physicians with symptoms, medical therapy -namely, α-blockers and 5α-reductase inhibitors alone or in combination -is typically the fi rst-line treatment for men with BPH [ 16 ]. Current analysis of prescribing activity by Izard et al shows both widespread adoption of α-blockers, a gradual adoption of 5α-reductase inhibitors, and combination treatments by internists and family physicians [ 28 ]. Additional medications have FDA approval for LUTS, including anticholinergic medications and more recently PDE-5 inhibitors and β-receptor agonists.…”
Section: Monopolar Turp and Medical Therapymentioning
confidence: 99%
“…In a retrospective review, authors estimated that in 2008 at their center, 87 % of patients undergoing TURP had been previously treated with medical therapy for BPH [ 28 ]. This is in stark contrast to the 36 % of men in 1998.…”
Section: Monopolar Turp and Medical Therapymentioning
confidence: 99%
“…In a small RCT comparing HoLEP with holmium laser bladder neck incision (HoBNI) for prostates less than 40 g, 79% of patients having Urinary retention. It has been reported that the proportion of men having BPH surgery for urinary retention has increased over the last two decades [Izard and Nickel, 2010], and that TURP for men in urinary retention is associated with significant morbidity [Gujral et al 2000;Chacko et al 2001]. A recent American study reported a rise in the prevalence of BPH-associated acute renal failure of >400% between 1998 and 2008 [Stroup et al 2011].…”
Section: Bipolar-turp (B-turp)mentioning
confidence: 99%